Push-notiser för trädgårdsapplikationen Gardenize - Inventering av vädertjänster och implementation av systemlösning - Karlsson, Linda (My University, 2016)
The start-up company Gardenize is developing an Andriod application for gardeners and growers in cooperation with Tritech Gothenburg AB. This application will make garden work easier, thanks to documentation and smart reminders. There was a need to develope a finction that link weather information to the application Gardenize. This report covers diffrent weatherservices and tools required to make clecer weather-reminders work, and describes how the chosen tolls work together. The projcet was both a develpement- and research-project, since it was based on both product developement as well as research. Software based in the results of the investigation was programmed. The weather service fom MET was chosen for the project. Only one database was created and used for soring both forecasts and weather history. This database is written in MySQL. A server written in Java, which uses the tool Maven and Spring framework was created for comminucation between the Andriod application, the weather service, the GCM and the database. GCM was used too send push notifications to the unit where the Gardenize-application is installed. The HTTP protocol was used for communication between the server and GCM, and between the mobile application and the Java Server.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology